Consumer Driven Cereal Innovation : Where Science Meets Industry - Weegels, Peter (American Associate of Cereal Chemists International., 2009)
Consumer Driven Cereal Innovation: Where Science Meets Industry includes a collection of papers from oral and poster presentations, along with all the abstracts from the first Spring Meeting organized by Cereals & Europe, the European section of AACC International. These proceedings discuss the major innovation challenges the cereal industry is facing to meet consumers' demands and expectations. Consumers' needs are perhaps best summarized as foods that are safe, healthy, and tasty. This book helps answer important questions regarding these essential needs. With respect to safety, the cereal industry can already boast of an excellent reputation and a long tradition of safeguarding cereals and their products. But how can one define "healthyiA? How does one distinguish between reality and fiction? If the best ways to add health benefits to cereal products are to be determined, the consumer's palate needs first to be pleased. What are the most cost-effective ways to manufacture grain-based products for safety, health, and palatability? This conference addressed these important questions and this book is the result of the research and insights of many of the brightest minds in grain science today. Areas of Focus - Consumer Driven Cereal Innovation Conference Proceedings Plenary - Papers from Invited Lecturers: Consumer Attitudes Towards Healthy Cereal Products Consumer, Cereals and Health: Trends, Fads and Reality Health Benefits of Whole Grain Products Science Track: Consumer Insights and Nutritional Aspects of Innovative Cereal-based Products - Nutritional and Sensory Quality - Physiology Cereals: Source of High Quality Nutrients - Regulation and Functional Nutrients - Methodology Technology Track: Better processes for Better Nutrition Bioactive Ingredients Product Quality - Product Texture and Quality - Shelf Life - Toxicology.